2017
DOI: 10.1016/j.arthro.2017.08.229
|View full text |Cite
|
Sign up to set email alerts
|

Editorial Commentary: The Acrid Bioscrew in Anterior Cruciate Ligament Reconstruction of the Knee

Abstract: Bioresorbable screws have been widely adopted for graft fixation in knee anterior cruciate ligament (ACL) reconstruction on the promise of screw resorbtion and replacement by bone. When considering the value of bioresorbable screws, it is imperative to understand that the "A" in PGA and PLA, the base ingredient of all bioscrews, is for Acid. All resorb by a process of hydrolysis; the speed and extent of resorbtion is determined by both the acidity of the screw and the environment in which it is placed. Regrett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…21 Karikis et al 22 reported that 83% of patients 5 years after hamstring ACL reconstructions secured with selfreinforced SR-PL (96)/D (4) LA/b-TCP biocomposite interference screws had decreased tibial tunnel widths compared with the early postoperative period. As Pinczewski and Salmon 23 noted, biocomposite material reabsorption also may be influenced by the environment into which it is implanted, with the potential for different performance in different locations.…”
Section: Discussionmentioning
confidence: 99%
“…21 Karikis et al 22 reported that 83% of patients 5 years after hamstring ACL reconstructions secured with selfreinforced SR-PL (96)/D (4) LA/b-TCP biocomposite interference screws had decreased tibial tunnel widths compared with the early postoperative period. As Pinczewski and Salmon 23 noted, biocomposite material reabsorption also may be influenced by the environment into which it is implanted, with the potential for different performance in different locations.…”
Section: Discussionmentioning
confidence: 99%
“…У відповіді на публікацію в журналі Arthroscopy редактори висловили власне розчарування імплантатами, що піддаються біодеградації, які, на їх думку, не виправдали покладених на них очікувань та не підтвердили позитивних результатів експериментальних досліджень на тваринах, і висловилися на користь більш перспективного розвитку PEEK імплантатів, як більш біологічно інертних, що не викликають реактивного запального процесу [38].…”
Section: матеріали і методиunclassified
“…Although bioresorbable screws have been associated with good clinical outcomes and do not cause MRI signal flare, resorption has proven unreliable and complete replacement by bone rare 5 . This is largely due to the acidic nature of the materials and the hydrolytic pathway for their dissolution resulting in bony destruction and cyst formation 3,20 .…”
Section: Introductionmentioning
confidence: 99%
“…5 This is largely due to the acidic nature of the materials and the hydrolytic pathway for their dissolution, resulting in bony destruction and cyst formation. 3,19 Another option is polyether ether ketone (PEEK), a thermoplastic polymer that is widely used in spinal and maxillofacial surgery and is becoming increasingly popular in orthopaedic surgery. PEEK is chemically inert and insoluble, has a modulus of elasticity closer to human cortical bone, is compatible with MRI, and, for sterilization purposes, has high resistance to radiation.…”
mentioning
confidence: 99%